The influence of device physics on organic magnetoresistance - Cox, Mark G. D. M.; Janssen, Paul; Wouters, S. H. W.; van der Heijden, E. H. M.; Kemerink, Martijn; Koopmans, Bert (Synthetic metals, 2013)
In order to explain the surprisingly large, low field organic magnetoresistance (OMAR), several microscopic mechanisms have been proposed recently, but their effect on the polaron transport through a realistic device is relatively unknown. Here we study the effect of device physics on all proposed mechanisms, using a numerical drift-diffusion simulation method. We implement the local magnetic field dependent reactions via a magnetic field dependent recombination, mobility and triplet formation rate. Furthermore, a novel approach is used where we keep track of the subsequent particles formed from these reactions, including excitons and trions. We find that even in the most straightforward device structure sign changes can occur due to device physics. Especially the transition from a diffusion dominated to a drift dominated current near the built-in voltage plays a crucial role for understanding organic magnetoresistance. Finally, we conclude that the shape of the magnetocurrent as a function of voltage can be used as a fingerprint for the underlying dominant microscopic mechanism governing OMAR in a device.